Predictive mechanism of a modified bug controller for mobile robot path navigation. (28th April 2022) - Mukherjee, Subhradip; Kumar, Rajagopal; Borah, Siddhanta
Bug approaches are popular for mobile robot navigation in challenging environments. Traditional bug approach follows a virtual straight line from source to target location and exhibits obstacle boundary. This behaviour of the bug approach consumes more travel time towards target location. In addition, obstacles with larger size situated in central-left or central-right side of the virtual straight line between source and target location create navigation problems for bug approaches. A modified bug (m-Bug) controller has been proposed and realised for mobile robot path navigation with a better solution in MATLAB and V-REP simulation environments. With range sensors, the proposed controller was found to exhibit better-optimised travel time and path length in the given environments. Different static environments with single and multiple obstacles have been considered for testing the proposed controller. Various simulation results and comparative analysis highlight the superiority of the controller.